Susan Hammer at Paradise Club. - Sahl, Ted (photographer):::Creator::::::::::::
Mayoral candidate, Susan Hammer, at a fundraiser held at the Paradise Club. From left to right are Sal Accardi, Susan Hammer and Jon Snell.